Penerapan Metode Fuzzy Mamdani untuk Menentukan Jumlah Pendapatan Pegadaian Berdasarkan Jumlah Omset Harga Emas dan Kurs - Rahmawati; Rahima Dina; Wartono (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2020)
Corporate planning in determining the amount income decision making for the period based on turnover, gold and exchange rates at the Pegadaian Syariah Branch Subrantas Sidomulyo Unit Pekanbaru. The Purpose of this study is to investigate the use of fuzzy logic aplication using Mamdani methos for dicision making determination of total income. The results of this study indicate that the prediction of income with accuracy reaches 87,4632%.